The synthesis of water-soluble CDM-AM copolymer by irradiation and its solubilization effect on hydrophobic drugs - Yong-Fu Li; Hong-Tao Tang; Si-Jing Zhou (Designed Monomers and Polymers, 2018)
The β-cyclodextrin-acrylamide (CDM-AM) copolymer was prepared from acrylamide and β-CD maleate (CDM) using 60Co γ-ray irradiation method. The optimized preparation conditions for the CDM-AM copolymer are as follows: CDM:AM mass ratio of 1:1; irradiation dose of 4 kGy; and using 20 mL of DMF water solution. The yield rate of CDM-AM was 75% in grams using these synthetic conditions. The effects of the CDM-AM copolymer on the solubility and fungicidal activity of natamycin (NM) and carbendazim (MBC) were investigated. The stability constant of NM·CDM-AM and MBC·CDM-AM complexes at 303 K were of 13,446.06 M−1 and 2595.3 M−1, respectively. The complexes were characterized using phase solubility diagrams, NMR spectra and FT-IR spectra. The analysis of the biological activities of these two complexes indicated that they possessed enhancing fungicidal activities compared to NM and MBC alone.